2012
DOI: 10.1037/a0030319
|View full text |Cite
|
Sign up to set email alerts
|

Individual-level consistency of different laterality measures in the goldbelly topminnow.

Abstract: In humans, hemispheric language dominance is, to some degree, associated with handedness. Significant associations have been reported between several other lateralized functions. Much less is known about the organization of cerebral asymmetries in nonhuman species and, in particular, whether the presence of reversed asymmetry of one function is associated with a reversal of other lateralized functions or, instead, if cognitive functions lateralize independently. In this study, we compare four measures of senso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
0
11
1
Order By: Relevance
“…Previous investigation in Girardinus falcatus has identified a negative association in visual laterality between two methods (quasicircular mirror maze assay and detour assay with predator valence: r = − 0.440) and motor laterality between two methods (spontaneous turns in the dark and rotational preference: r = − 0.341). However, no relationship was identified between these types of lateralisation (r = − 0.068-0.167) (Dadda et al 2012). The social 'visual' quasi-circular mirror maze assay, which was found to produce lateralisation indexes uncorrelated with those from either 'motor' assay in our study, demonstrated a greatly reduced level of variation between individuals and no apparent asymmetry in monocular eye-use.…”
Section: Discussioncontrasting
confidence: 64%
“…Previous investigation in Girardinus falcatus has identified a negative association in visual laterality between two methods (quasicircular mirror maze assay and detour assay with predator valence: r = − 0.440) and motor laterality between two methods (spontaneous turns in the dark and rotational preference: r = − 0.341). However, no relationship was identified between these types of lateralisation (r = − 0.068-0.167) (Dadda et al 2012). The social 'visual' quasi-circular mirror maze assay, which was found to produce lateralisation indexes uncorrelated with those from either 'motor' assay in our study, demonstrated a greatly reduced level of variation between individuals and no apparent asymmetry in monocular eye-use.…”
Section: Discussioncontrasting
confidence: 64%
“…There are two lines of reasoning that allow us to discount this possibility. Firstly, previous studies have shown strong associations between various tests of laterality in this and other species (Dadda et al, 2012 ). Thus the outcome would likely to have been the same even if we had examined laterality using an alternative assay (Bisazza et al, 1997 ).…”
Section: Discussionmentioning
confidence: 71%
“…Seventy subjects were observed in this test. We employed the same apparatus described elsewhere (Dadda et al, 2012 ; Figure 1A ). Briefly, the fish was placed in a clear cylinder in the center of an octagonal tank with mirrored walls.…”
Section: Methodsmentioning
confidence: 99%
“…However, hemispheric use is task dependent [24], and we measured social lateralization [14,16]. This is expected to correlate with inhibitory control lateralization, but it does not necessarily predict the hemisphere involved [15]. Patterns of neural activity, which can be measured in larvae, are necessary to answer this question.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we measured it using a social task. Because lateralization of different cognitive functions is correlated in individuals [15,16], our social lateralization measure provided a proxy for overall individual differences in lateralization, including those of inhibitory control functions. Zebrafish were observed for 20 min in an octagonal apparatus with mirror walls (electronic supplementary material, figure S1).…”
Section: Methodsmentioning
confidence: 99%